Preventive oral surgery before bisphosphonate administration to reduce osteonecrosis of the jaws. (13th January 2014) - Mozzati, M; Maggiora, M; Scoletta, M; Vasta, A; Canuto, RA; Muzio, G
<x xml:space="preserve">Abstract</x> Objectives The intravenous injection of bisphosphonates, currently used for osteoporosis, myeloma, or bone metastases, can cause ONJ especially in consequence of trauma. To avoid trauma during bisphosphonate treatment, preventive oral surgery is recommended. The research aimed to evidence whether inflammatory and osteoclastogenic factors are not induced in oral mucosa after bisphosphonate treatment in patients receiving oral preventive surgery procedure and whether proliferation factors are not inhibited. Patients and Methods Specimens of oral mucosa were removed from healthy subjects and from patients undergoing preventive oral surgery before bisphosphonate treatment. The expression of cytokines and factors involved in osteoclast activity, cell proliferation, and angiogenesis were examined. Results Cytokines and RANK‐L levels decreased significantly in mucosa from patients undergoing preventive oral surgery procedure before bisphosphonate treatment in comparison with their levels at the beginning of procedure and also in comparison with the level in patients treated only with bisphosphonates and not developing ONJ; conversely, osteoprotegerin and hydroxymethylglutaryl coenzyme A reductase significantly increased or not changed. Conclusions The results suggest that preventive oral surgery could be able to prevent ONJ due to bisphosphonate treatment: The mucosa is not stimulated by bisphosphonates to cause ONJ, as bisphosphonates are probably not released from the bone.